2011
DOI: 10.3844/ajessp.2011.456.462
|View full text |Cite
|
Sign up to set email alerts
|

Geo-Spatial Technologies for Carbon Sequestration Monitoring and Management

Abstract: Problem statement: Globally, the quantification of Carbon Sequestration (CS) potential of various ecosystems was a challenge. There was an urgent need for technologies that can quantify CS potential cost-efficiently in a repeated and organized manner. Approach: Remote Sensing (RS) and Geographic Information System (GIS) had great potential in current estimation, future prediction and management of carbon sequestration potential in terrestrial ecosystems. This review discusses the current utilization of RS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Terrestrial vegetation and soil represents important sources and sinks of atmospheric carbon [8]. The quantification of CS potential of various ecosystems is a challenge [9]. Forests sequester and store large amounts of atmospheric carbon and thus play a key role in the mitigation of climate change [10].…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial vegetation and soil represents important sources and sinks of atmospheric carbon [8]. The quantification of CS potential of various ecosystems is a challenge [9]. Forests sequester and store large amounts of atmospheric carbon and thus play a key role in the mitigation of climate change [10].…”
Section: Introductionmentioning
confidence: 99%
“…Goetz et al, 2009). The review byJeyanny et al, 2011 discusses the current utilization of RS and GIS technologies in CS management in various sectors Niu and Duiker (2006). reported that Landsat imagery integrated into a GIS was used to identify hotspots (i.e., high CS capacity locations) for afforestation programs in the USA.…”
mentioning
confidence: 99%